Internalisasi Nilai Religius Pendidikan Agama Islam dalam Keterampilan Berbahasa Peserta Didik - Lalu Surya Jagat; Runi Fazalani; Ni Wayan Sadiyani (STKIP Subang, 2025)
This study aims to describe the process of internalizing religious values of Islamic Religious Education in students’ language skills learning at the elementary school level. This research employed a qualitative approach with a field research design. The research subjects included Islamic Religious Education teachers, classroom teachers/Indonesian language teachers, and elementary school students. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the internalization of religious values in language skills learning occurs through several stages, namely the introduction of religious values, understanding of values, reinforcement and habituation, and value internalization reflected in students’ language behavior. Religious values were internalized through teacher role modeling, the use of polite language, selection of texts containing Islamic values, and habituation of respectful language use in classroom interactions. This process positively contributes to the development of students’ religious character, particularly in terms of politeness, honesty, and responsibility in language use. The study implies that language skills learning should be integratively designed with Islamic Religious Education to strengthen students’ religious character in elementary schools.